2020
DOI: 10.3390/nano10030402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amorphous Silica Nanopowders on the Avoidance Behavior of Five Soil Species—A Screening Study

Abstract: Silica nanoparticles (SiO2NPs) are one of the most used in commercial products and biomedical tools, however, their environmental effects have not been fully described. Although negative effects of SiO2NPs on the behavior of freshwater invertebrates have been reported, the knowledge is limited, especially the effect of nanopowders in terrestrial organisms. Accordingly, the aim of the present study is to understand the effects of SiO2NPs on the avoidance behavior of five soil species, whose niche may differ thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Likewise, in maize, field applications of SiO 2 -NPs resulted in a large improvement to growth, but interestingly, there were disruptive effects as well with the Si found to induce a pesticide response for the crop during storage [107]. Similarly, some soil invertebrates demonstrate avoidance behaviors to SiO 2 NP Santos et al [108], and it has been shown that they can increase soil bacteria community diversity [109].…”
Section: Limitations and Considerations For Fmsn Use In Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in maize, field applications of SiO 2 -NPs resulted in a large improvement to growth, but interestingly, there were disruptive effects as well with the Si found to induce a pesticide response for the crop during storage [107]. Similarly, some soil invertebrates demonstrate avoidance behaviors to SiO 2 NP Santos et al [108], and it has been shown that they can increase soil bacteria community diversity [109].…”
Section: Limitations and Considerations For Fmsn Use In Soilsmentioning
confidence: 99%
“…SiO 2 NP place within the top five commercial nanoproducts globally [ 108 , 110 ] with applications ranging from paint stabilizers through to food agents [ 111 ]. Therefore, extensive material flows of SiO 2 NP into the environment are already ongoing [ 111 ].…”
Section: Limitations and Considerations For Fmsn Use In Soilsmentioning
confidence: 99%
“…The avoidance response is considered an extremely relevant ecological endpoint, because if the organisms avoid a contaminated soil, the services provided by them will be compromised and the habitat function declines, negatively affecting the soil ecosystem [ 20 , 21 , 22 , 23 ]. On the other hand, if the organisms are not able to avoid the contaminated soil, the hazard on the organisms may be much higher [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The avoidance response is considered an extremely relevant ecological endpoint, because if the organisms avoid a contaminated soil, the services provided by them will be compromised and the habitat function declines, negatively affecting the soil ecosystem [ 20 , 21 , 22 , 23 ]. On the other hand, if the organisms are not able to avoid the contaminated soil, the hazard on the organisms may be much higher [ 23 , 24 , 25 ]. Studies were performed assessing the avoidance behavior of soil organisms (e.g., Eisenia fetida , Enchytraeus crypticus , Porcellionides pruinosus , Porcellio scaber and Tenebrio molitor ) when exposed to NPs-contaminated soil [ 20 , 22 , 23 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation